Development of Supervision Instrument Application Model through the Utilization of Android-Based Technology for School Heads - Purnamawati, Risa Fahriyani; Hidayat, Rais; Suharyati, Henny (iora, 2020)
Indonesia needs to improve the teacher’s competence in terms of personality, social, pedagogic and professional dimension since the student’s achievement is still under satisfied. Learning supervision is one of the competences which the principal should have to improve the teacher’s performance. Observation and data analysis of the learning supervision are the important components to create such qualified information. The research is intended to develop manual based observation to be Android based observation by research and development method, to analyze and empirically proof the model quality and accountability. The research fact of model quality is based on the assessment of supervision, output, linguistics, usage, software engineering, design, and visual communication aspects. Data analyzing technique uses qualitative approach through inductive method while data collecting technique uses observation model of 11 principals research subject at Gugus 04 of District Cisarua Kabupaten Bogor. The research produce Android based observation namely AOS (Application of Observation) with the accountability index 4.57 which means that the model is accountable to be used at learning supervision process so that the quality of the learning process and the student performance can be improved.